2018
DOI: 10.1016/j.jnutbio.2017.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Colonic aberrant crypt formation accompanies an increase of opportunistic pathogenic bacteria in C57BL/6 mice fed a high-fat diet

Abstract: The increasing worldwide incidence of colon cancer has been linked to obesity and consumption of a high-fat Western diet. To test the hypothesis that a high-fat diet (HFD) promotes colonic aberrant crypt (AC) formation in a manner associated with gut bacterial dysbiosis, we examined the susceptibility to azoxymethane (AOM)-induced colonic AC and microbiome composition in C57/BL6 mice fed a modified AIN93G diet (AIN, 16% fat, energy) or an HFD (45% fat, energy) for 14 weeks. Mice receiving the HFD exhibited inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 77 publications
0
50
0
Order By: Relevance
“…This result is consistent with previous literatures. One study showed a decrease of Barnesiella , a SCFA-producing bacteria, in the colon of HFD-fed mice, which may be linked to the gut inflammatory phenotype in azoxymethane-induced colon cancer ( Zeng et al, 2018 ). Likewise, the present study shows the age-specific reduction of potentially beneficial Barnesiella spp.…”
Section: Resultsmentioning
confidence: 99%
“…This result is consistent with previous literatures. One study showed a decrease of Barnesiella , a SCFA-producing bacteria, in the colon of HFD-fed mice, which may be linked to the gut inflammatory phenotype in azoxymethane-induced colon cancer ( Zeng et al, 2018 ). Likewise, the present study shows the age-specific reduction of potentially beneficial Barnesiella spp.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to an elevated level of secondary BAs, consumption of a high-fat diet not only increases inflammatory status but also accompanies an increase of opportunistic pathogenic bacteria in the mouse colon [49,157]. Colonic inflammation and cancer are multifactorial disorders that may be affected by the complex interactions between genetics, diet, the gut microbiome, and other factors [158,159].…”
Section: Secondary Bas Scfas Oncomicrobes and Colon Cancermentioning
confidence: 99%
“…The reduction of Anaeroplasmataceae could decrease the pathogenesis of depression. In the study of colon cancer, Zeng et al [59] found that the abundance of Anaeroplasma increased in the HFD-azoxymethane (AOM) group. The Anaeroplasma bacteria is negative by Gram stain, which belongs to Mollicutes class, Tenericutes phylum.…”
Section: Discussionmentioning
confidence: 99%